Elucidation of Factors Affecting Anterior Occlusion in Primary Dentition Based on the Japan Environment and Children’s Study - Risa Ishiko; Kotaro Sena; Ichie Koseki; Masumi Sasai; Chiharu Ota; Takeyoshi Koseki (Children)
Background/Objectives: Malocclusion in primary dentition affects permanent dentition. However, the factors contributing to malocclusion in the oral cavities of children have not been fully elucidated. We hypothesized that environmental factors affect malocclusion in the primary dentition of the Japanese population and aimed to identify factors associated with anterior occlusion in primary dentition. Methods: The study involved 3793 parent–child pairs from the Miyagi Regional Centre as part of a supplementary survey to the Japan Environment and Children’s Study, a cohort study. A questionnaire assessing oral development and environmental factors was administered to parent-child pairs who consented to participate. Parents assessed anterior occlusion when their children were 3.5 years old. Results: The maxillary primary central incisors tended to erupt earlier in the open bite group. Significantly more children in this group were breastfed until 1 year and drank ionic beverages at 1.5 years. In addition, thumb sucking or pacifier use was significantly common at 2 years of age. A correlation was observed between the mother’s body mass index (BMI) before and after pregnancy and anterior occlusion. Conclusions: In the open bite group, the occlusion status of the anterior teeth at 3.5 years of age showed distinctive results influenced by the eruption period of the primary anterior teeth, oral habits, intake of sweetened beverages, and maternal BMI. These findings suggest that parental observation could be useful for screening children for malocclusion until the eruption of permanent dentition.